Analisis prioritas faktor kendaraan, manusia, dan jalan terhadap kecelakaan lalu lintas di koridor inspeksi Kalimalang, Bekasi - Nur Wulan Sari; Adenanthera Lesmana; Roesjanto Roesjanto (Logistics and Supply Chain Insights, 2025)
The rapid development and population growth in Bekasi Regency, Indonesia, have resulted in increasing traffic density and a corresponding rise in road traffic accidents (RTA), particularly along the critical 28 km Kalimalang Inspection Highway, locally known as "Jalur Tengkorak." This study aims to analyze the simultaneous and partial influence of Vehicle Factors (X1), Human Factors (X2), and Road Physical Condition Factors (X3) on RTA (Y). A quantitative descriptive approach utilizing Multiple Linear Regression (MLR) was employed, based on primary data collected through questionnaires from 100 motorcycle riders and secondary data from Polresta Bekasi (2022). The findings confirm that all three variables significantly and positively influence RTA, resulting in the model \hat{Y} = 2.218 + 0.302 X1 + 0.161 X2 + 0.289 X3 + μ. The adjusted coefficient of determination (R^2) is 0.514, indicating that 51.4% of RTA variation is explained by these factors. Crucially, the Road Physical Condition Factor (X3) emerged as the strongest predictor (t=4.429, β=0.385), surpassing the traditional dominance of human error. This key finding suggests that mitigation strategies must prioritize urgent infrastructure repair addressing potholes, road waves, and insufficient markings to significantly reduce accident frequency in this corridor.